(untitled) (Al-Academy, 2021)
The art of synthesis is one of the most important pillars in cinematic art, as the director combines cinematic shots to produce a third shot in the mind of the recipient by various methods such as mental synthesis, analogous synthesis, rhythm synthesis, parallel synthesis and repetitive synthesis, Repetitive synthesis is one of the most important techniques in cinematic montage. Through repetitive synthesis, the director is able to link the shots and scenes with each other, and this is what we see in the poetic imagery of Adnan Al-Sayegh when he links the visual images to each other, especially those images that manifest the manifestations of grief and misery following the misfortunes that befell in His homeland. This study follows the descriptive-analytical approach, to show the repeated synthesis in the folds of the goldsmith’s poems with the intention of determining the goal that the poet aims to by repeating the specific shot in the poem, whether the shot is audio or visual, to confirm a specific idea and from this point of view this research revolves around several main axes ; Repeat Single Shot, Repeat Sound Shot, Repeat Cinematic Image Dimension.